Clinicopathological study of 229 cases of salivary gland tumors in Isfahan population - Nakisa Torabinia; Saeedeh Khalesi (Wolters Kluwer Medknow Publications, 2014)
Background: Salivary gland tumors are relatively uncommon and they consist of 3-10% of head and neck neoplasms. Most of studies have shown geographic variation in the incidence and histopathologic types of salivary gland neoplasms. The aim of this study was to evaluate the salivary gland tumors in Isfahan for 10 years duration. Materials and Methods: In this epidemiological study, 229 medical records of patients with salivary gland neoplasms in Isfahan for 10 years duration (January 2001-December 2011) were reviewed. The clinical data and histopathological features were statistically analyzed using the Chi-square, analysis of variance and Fisher tests; P < 0.05 was considered to be significant. Results: The data showed that salivary gland tumors were most frequent in women. The mean age of patients with benign tumors was 41.26 years and 51.83 years in malignant tumors. Out of 229 salivary gland neoplasms, 127 (55.5%) were benign and 102 (44.5%) were malignant. Most were in parotid (105), followed by the minor salivary glands (95), the submandibular gland (28) and the sublingual gland (1). Conclusion: Pleomorphic adenoma is the most common salivary gland tumor and mucoepidermoid carcinoma followed by adenoid cystic carcinoma are the most common malignancy of salivary gland tumors in Isfahan population. Although most of the results of this study were similar to those reported in other populations, some differences were observed.